Personality traits and physical activity in patients with gambling disorder attending a rehabilitation center. An observational study - Fierro, Inmaculada; Fernández-Prieto, Raúl; Fernández-Parra, Alicia; Herrero-Martín, Miriam; Herrero, Azael J. (Frontiers in Psychology, 2024)
Objective: Problem gambling is associated with various negative health behaviors, such as physical inactivity. However, physical activity may also be used as a coping mechanism to manage stress and anxiety. This study aimed to investigate whether personality traits are associated with physical activity levels in individuals attending a rehabilitation center for gambling disorder (GD).Methods: An observational study was conducted in 71 patients belonging to a Gamblers' Recovery Association. All of them completed a socio-demographic questionnaire, the Exploratory Personality Questionnaire-III (CEPER-III) and the International Physical Activity Questionnaire (IPAQ). Comparisons with general population and association between personality traits and physical activity were analyzed.The study sample predominantly consisted of male participants (91.5%), with the majority having an educational attainment of compulsory schooling or less (70.4%). Additionally, a substantial proportion of participants exhibited school-related problems (43.7%) and had a history of mental health issues (33.8%). Compared to the general population, individuals in the CEPER-III cohort demonstrated significantly lower scores in the following personality traits: paranoid (p< 0.05), histrionic (p< 0.001), narcissistic (p< 0.001), passive-aggressive (p< 0.05), and sadistic (p< 0.01). Multivariate logistic regression analysis indicated that the antisocial, borderline, obsessive-compulsive, and self-destructive personality traits were significantly associated (p< 0.05) with the level of physical activity.This study found a link between personality traits and physical activity levels in patients with GD. Gamblers with higher scores on obsessive-compulsive and self-destructive personality traits were more likely to fall into the moderate-high physical activity group. In contrast, those with higher scores on antisocial and borderline personality traits were more likely to be classified in the low physical activity group.